Energy Efficient Operation of Three Phase Induction Motor using Delstar Converter for Machine Tools - M. Premkumar; R. Sowmya (International Journal of Electrical and Computer Engineering (IJECE), 2017)
DELSTAR converter is an electronic system to be interfaced with the existing STAR – DELTA starter for machine tools. Induction motor consumes more power while it is operated at DELTA mode for a long time under no load condition. The proposed system gives the solution for the above stated problem. When the load on the motor is less than 40% of full load, it switches the motor to operate in STAR mode to save energy. When the load increases beyond 40%, it automatically switches the motor to operate in DELTA mode. The starting regimen is not disturbed. The proposed converter is recommended for applications where load changes are not more than 120 times/hour. This can be used with any capacity motor by choosing appropriate current transformers and setting the current level using the potentiometer built in. The proposed converter is designed for 5HP induction motor and experimentally tested.